THE SEMANTIC ROLE OF KOREAN CONJUNCTIONS AND THEIR EXPRESSION IN UZBEK (International journal of artificial intelligence, 2025)
The study explores the semantic roles of conjunctions in the Korean language and examines their equivalents in Uzbek. It analyzes the functions these conjunctions perform within sentence structures, considering their syntactic and semantic nuances. Through comparative linguistics, this article aims to shed light on the similarities and differences between the two languages' conjunctional use, providing insights into syntactic structures and cultural contexts.